Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A, 3/9 + 9/15 + 8/12
= 1/3 + 9/15 + 2/3
= 8/5
B, 4/10 + 12/32 + 9/15
= 2/5 + 3/8 + 9/15
= 11/8
\(\frac{3}{9}+\frac{9}{15}+\frac{8}{12}=\frac{1}{3}+\frac{3}{5}+\frac{2}{3}=\left(\frac{1}{3}+\frac{2}{3}\right)+\frac{3}{5}=1+\frac{3}{5}=\frac{8}{5}\)
\(\frac{4}{10}+\frac{12}{32}+\frac{9}{15}=\frac{2}{5}+\frac{3}{8}+\frac{3}{5}=\left(\frac{2}{5}+\frac{3}{5}\right)+\frac{3}{8}=1+\frac{3}{8}=\frac{11}{8}\)
\(\left(\frac{4}{10}-\frac{8}{30}\right)\times\frac{6}{8}=\frac{2}{15}\times\frac{3}{4}=\frac{6}{60}=\frac{1}{10}\)
1.
a) \(\frac{16}{24}-\frac{1}{3}=\frac{16}{24}-\frac{8}{24}=\)\(\frac{8}{24}=\frac{1}{3}\)
b) \(\frac{4}{5}-\frac{12}{60}=\frac{48}{60}-\frac{12}{60}=\frac{36}{60}=\frac{9}{15}\)
3.
a)\(\frac{17}{6}-\frac{2}{6}=\frac{17-2}{6}=\frac{15}{6}\)
b) \(\frac{16}{15}-\frac{11}{15}=\frac{16-11}{15}=\frac{5}{15}=\frac{1}{3}\)
c) \(\frac{19}{12}-\frac{13}{12}=\frac{19-13}{12}=\frac{6}{12}=\frac{1}{2}\)
a) 16 24 − 1 3 = 16 24 − 8 24 = 24 16 − 3 1 = 24 16 − 24 8 = 8 24 = 1 3 24 8 = 3 1 b) 4 5 − 12 60 = 48 60 − 12 60 = 36 60 = 9 15 5 4 − 60 12 = 60 48 − 60 12 = 60 36 = 15 9 3. a) 17 6 − 2 6 = 17 − 2 6 = 15 6 6 17 − 6 2 = 6 17−2 = 6 15 b) 16 15 − 11 15 = 16 − 11 15 = 5 15 = 1 3 15 16 − 15 11 = 15 16−11 = 15 5 = 3 1 c) 19 12 − 13 12 = 19 − 13 12 = 6 12 = 1 2 12 19 − 12 13 = 12 19−13 = 12 6 = 2 1
\(a)\frac{3}{4}+\frac{1}{3}+\frac{2}{5}=\frac{45+20+24}{60}=\frac{89}{60}\)
\(b)\)Rút gọn rồi tính
\(a)\frac{3}{18}+\frac{4}{7}=\frac{1}{6}+\frac{4}{7}=\frac{7+24}{42}=\frac{31}{42}\)
\(b)\frac{12}{24}+\frac{12}{15}=\frac{1}{2}+\frac{4}{5}=\frac{5+8}{10}=\frac{13}{10}\)
$\frac{{15}}{6} = \frac{{15:3}}{{6:3}} = \frac{5}{2}$
$\frac{{12}}{{16}} = \frac{{12:4}}{{16:4}} = \frac{3}{4}$
$\frac{{35}}{{105}} = \frac{{35:35}}{{105:35}} = \frac{1}{3}$
\(\dfrac{15}{35}+\dfrac{7}{10}=\dfrac{3}{7}+\dfrac{7}{10}=\dfrac{30}{70}+\dfrac{49}{70}=\dfrac{79}{70}\)
\(\dfrac{27}{72}+\dfrac{11}{24}=\dfrac{3}{8}+\dfrac{11}{24}=\dfrac{9}{24}+\dfrac{11}{24}=\dfrac{20}{24}=\dfrac{5}{6}\)
\(\dfrac{6}{12}+\dfrac{7}{6}=\dfrac{1}{2}+\dfrac{7}{6}=\dfrac{3}{6}+\dfrac{7}{6}=\dfrac{10}{6}=\dfrac{5}{3}\)
4/5 nha bn
kết quả là 4/5 nha